Pengaruh persepsi risiko dan dukungan psikososial terhadap perilaku pencegahan kecemasan pasien penyakit kronis - Ilne Ai Purana Adel; Hanggara Budi Utomo; Ninik Setiyowati; Elin Hidayat (Jurnal Ners, 2025)
Background: Anxiety is commonly experienced by patients with chronic illnesses and can affect their decision-making and quality of life. Factors such as risk perception and psychosocial support play a crucial role in determining anxiety levels; however, the relationship between these factors has not been widely studied. Methods: This research employed a cross-sectional design using a quantitative approach. The sample consisted of 102 patients with chronic illnesses registered at Undata General Hospital, selected through stratified random sampling. Data were collected using a structured questionnaire measuring risk perception, psychosocial support, and anxiety prevention behavior. Data analysis was performed using multiple linear regression after conducting classical assumption tests. Results: Risk perception and psychosocial support were found to have a significant influence on anxiety prevention (F = 8.586; p < 0.05). Risk perception had a negative effect on anxiety prevention (B = -0.277; p = 0.006), while psychosocial support had a positive effect (B = 0.265; p = 0.007). Both variables explained 14.8% of the variance in anxiety prevention behavior. Conclusion: Strong psychosocial support can help reduce anxiety in patients with chronic illnesses, while high risk perception tends to increase it. Appropriate education and the strengthening of social support may serve as effective strategies to enhance patients' ability to manage anxiety. Therefore, integrating physical and psychosocial management in chronic disease care is essential.